Motivational drivers of repeat tourism to South Korea: The role of Hallyu - Saad, Mazni Binti; Nimer, Abukhalifeh Alaa; Ahmad, Siti Yuliandi; Husin, Nor Azilah (Journal of Tourism Management Research, 2025)
Hallyu and revisit intentions have been highlighted as important research topics in the competitive market of tourism destinations. Despite extensive research on repeat visitors, it remains unclear why people undertake repeat visits and what characteristics define repeat visitors. Using the Stimulus-Organism-Response model, this research aims to identify the Hallyu-relevant factors that influence non-Korean revisit intention to South Korea. A mixed-methods design was employed, collecting 222 data points, with 88% deemed usable. An open-ended question was analyzed through thematic analysis to explore tourists' impressions after their visits. The qualitative results indicated that K-cuisine, K-drama scenery, K-pop music, and K-drama celebrities leave a strong impression on international tourists. The regression model explained 63% of the variance, demonstrating the significant influence of Hallyu on revisit intention. The standardized beta coefficients showed that K-beauty products (Beta = .314, t = 4.267, p < .001) and K-cuisine (Beta = .251, t = 3.372, p < .001) were the most influential predictors. From the perspective of non-Korean visitors, K-cuisine and K-beauty products are key factors driving their desire to revisit South Korea. This cultural immersion through Hallyu promotes sustainable tourism, supports local economies, encourages cross-cultural exchange, and redefines destination loyalty. It shifts the focus from traditional tourism to fostering repeat visits and deeper cultural connections, thereby enhancing the overall tourism experience and long-term destination appeal.